HDL biodistribution and brain receptors in zebrafish, using HDLs as vectors for targeting endothelial cells and neural progenitors - Sulliman, Nora Cassam (Sci Rep, 2021)
High density lipoproteins (HDLs) display pleiotropic functions such as anti-inflammatory, antioxidant, anti-protease, and anti-apoptotic properties. These effects are mediated by four main receptors: SCARB1 (SR-BI), ABCA1, ABCG1, and CD36. Recently, HDLs have emerged for their potential involvement in brain functions, considering their epidemiological links with cognition, depression, and brain plasticity. However, their role in the brain is not well understood. Given that the zebrafish is a well-recognized model for studying brain plasticity, metabolic disorders, and apolipoproteins, it could represent a good model for investigating the role of HDLs in brain homeostasis. By analyzing RNA sequencing data sets and performing in situ hybridization, we demonstrated the wide expression of scarb1, abca1a, abca1b, abcg1, and cd36 in the brain of adult zebrafish. Scarb1 gene expression was detected in neural stem cells (NSCs), suggesting a possible role of HDLs in NSC activity. Accordingly, intracerebroventricular injection of HDLs leads to their uptake by NSCs without modulating their proliferation. Next, we studied the biodistribution of HDLs in the zebrafish body. In homeostatic conditions, intraperitoneal injection of HDLs led to their accumulation in the liver, kidneys, and cerebral endothelial cells in zebrafish, similar to that observed in mice. After telencephalic injury, HDLs were diffused within the damaged parenchyma and were taken up by ventricular cells, including NSCs. However, they failed to modulate the recruitment of microglia cells at the injury site and the injury-induced proliferation of NSCs. In conclusion, our results clearly show a functional HDL uptake process involving several receptors that may impact brain homeostasis and suggest the use of HDLs as delivery vectors to target NSCs for drug delivery to boost their neurogenic activity.